Nonhepatic Hyperammonemia With Septic Shock: Case and Review of Literature - Nishil Dalsania MD; Suhali Kundu MD; Ravi Karan Patti MBBS; Navjot Somal MBBS; Yizhak Kupfer MD (SAGE Publishing, 2022)
Elevated ammonia levels lead to cerebral edema, encephalopathy, seizures, coma, and death. Hyperammonemia is primarily associated with liver disease; however, there are rare cases without liver disease. Noncirrhotic hyperammonemia is primarily due to increased production and/or decreased elimination of ammonia. We present a rare case of a 35-year-old female with severe acute noncirrhotic hyperammonemia associated with gram-negative septic shock and a suspected undiagnosed partial urea cycle enzyme deficiency. She had elevated blood and urine amino acid levels speculated to be due to an underlying urea cycle defect, which was unmasked in the setting of septic shock with urea splitting bacteria leading to severely elevated ammonia levels. Ammonia levels were rapidly corrected with hemodialysis, as other conventional treatments failed. We highlight the importance of considering noncirrhotic causes of hyperammonemia in patients with elevated ammonia levels and intact liver function. Prompt treatment should begin with reducing the catabolic state, nitrogen scavenging, replacing urea cycle substrates, decreasing intestinal absorption, and augmented removal of ammonia with renal replacement therapy.